Wireless body area network (WBAN): A review of schemes and protocols. (2022) - Singh, Sunny; Prasad, Devendra
Abstract: To provide practical solutions to the difficulties faced by current available medicinal service based frameworks, Vital information of patient ought to be conveyed to the concerned destination continuously in real time by means of the web which gives rise to need to a system which allows any patient to get monitored over internet with the help of a network called as Wireless Body Area Network (WBAN) comprises of several sensor nodes that consume low power as compared to other sensing devices.. The utilization of these networks includes the assistance of human safety in various situations. Though WBAN is extremely useful in today scenario, several challenges need to be tackled before its deployment. This article provides a detailed study of various schemes and protocols used to deal with energy efficiency, fault tolerance, security and privacy. The study in this article also identifies challenges that need to be considered before the design and development of any protocol for WBAN.